2023
DOI: 10.3390/ph16040482
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Traditional Mexican Medicine and Their Applications as Antitumor Treatments

Abstract: Traditional medicine in Latin America and mainly in Mexico represents an essential alternative for treating different diseases. The use of plants as medicine is the product of a rich cultural tradition of the indigenous peoples, in which a great variety of species are used for the treatment of gastrointestinal, respiratory, and mental diseases and some other sicknesses; the therapeutic efficacy that they possess is due to the properties that derive from the active ingredients of plants principally antioxidants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…These findings align with the results reported by . Soto et al (2023) concluded that active plant components such as phenolic compounds, flavonoids, terpenoids, and tannins exhibit antioxidant properties. Moreover, Wu et al (2020) confirmed the strong antioxidant capacity of naphthoquinone compounds.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…These findings align with the results reported by . Soto et al (2023) concluded that active plant components such as phenolic compounds, flavonoids, terpenoids, and tannins exhibit antioxidant properties. Moreover, Wu et al (2020) confirmed the strong antioxidant capacity of naphthoquinone compounds.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Currently, there is a trend to promote the consumption of traditional foods due to their beneficial effects, which could potentially improve health. However, knowledge of the benefits is often based on observational studies and physiological arguments [8][9][10]. Among traditional Mexican foods is the flour obtained from Ramon seed, which is known as Maya nut.…”
Section: Introductionmentioning
confidence: 99%
“…Some trees were also utilized for construction purposes and herbal medicine. In the past year, there has been a screening of the antioxidant and anti-proliferative properties of underutilized Mexican plants; however, a limited description of the antioxidant compositions of these plant extracts was provided [8,9]. Interest in the antioxidant properties of plants has gained significant momentum in scientific research, owing to the growing awareness of the harmful effects of the free radicals and oxidative stress on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in the antioxidant properties of plants has gained significant momentum in scientific research, owing to the growing awareness of the harmful effects of the free radicals and oxidative stress on human health. Free radicals are unstable molecules that can damage cells and contribute to inflammation, thereby underpinning the development of diseases such as cancer, diabetes, and cardiovascular disorders [8,9].…”
Section: Introductionmentioning
confidence: 99%